Reproductive efficiency of Bos indicus (Zebu) cows under artificial insemination management in Ethiopia - Mukasa-Mugerwa, E.; Tegegne, Azage; Mesfin, T.; Teklu, Y. (Elsevier, 1991)
Analyses reproductive data on 4123 inseminations from 2332 breeding records of 1237 Arsi (Bos indicus) cows, collected between 1982 and early 1989 from the Gobe ranch of the Ethiopian Ministry of Agriculture where cows were kept under similar management; and concludes that long post partum anoestrus, poor oestrus detection and low conception rates contribute to extending calving intervals.